KAI Commuter Employee Development Application Using The Waterfall Method - Ramadan, Angga Riski; Junaidi, Agus; Azis, Mochammad Abdul (SAN Scientific, 2023)
The KAI Commuter Employee Development application is a solution to support employee development in the PT environment. Indonesian Commuter Train. The development method used in this project is the Waterfall Method, which is a sequential approach consisting of clear phases, including planning, analysis, design, development, testing, and implementation. This application aims to increase effectiveness and efficiency in the management and development of employees in the company. With features such as performance tracking, training, employee evaluation, and creating personal development plans, this application provides a powerful tool for management to monitor and improve the potential of their employees. The development process using the Waterfall Method allows developers to carefully detail requirements before starting the stage implementation. This ensures the application can meet predefined requirements well throughout the development cycle. In addition, this model allows for more structured progress monitoring and enables more efficient project management. By adopting the KAI Commuter Employee Development application and implementing the Waterfall Method, companies can develop their employees, increase productivity, and optimize resources for their humans.